MEASUREMENT OF READINESS AND INFORMATION TECHNOLOGY ADOPTION BASED ON ORGANIZATIONAL CONTEXT AMONG SMEs - Sani, Asrul; Nawangtyas, Nur; Budiyantara, Agus; Wiliani, Ninuk (Jurnal Pilar Nusa Mandiri, 2020)
The importance of using information technology forces organizations to switch to using this technology in the daily activities of the organization in running a business and this cannot be separated from the SMEs organization. This research was conducted to measure the readiness level of a Small, and Medium Enterprise (SMEs) organization in the use and adoption of information technology based on the organizational context. This research uses quantitative methods by conducting surveys and interviews with policymakers organized by SMEs to avoid inaccurate information. Surveys and interviews were conducted in the Jabodetabek area. Data will be processed using PLS-SEM software for statistical analysis and inferential analysis, while for descriptive analysis using SPSS and spreadsheets. The results obtained indicate a significant relationship between the readiness level variable and the IT adoption variable.